Possibility of a s-wave pairing in heavily Zn-doped YBa₂Cu₃O₇₋δ based on magnetic field effect on Andreev reflection spectra - Akimenko, A.I.; Gudimenko, V.A. (Физика низких температур, 2008)
When the dx₂₋y₂ -wave pairing is suppressed by Zn-doping in YBa₂Cu₃O₇₋δ some of the Andreev reflection spectra were found to be similar to the s-wave spectra of conventional superconductors. The energy gap is rather reproducible (2.3–3.0 meV). It is suppressed by low magnetic field (HcPC = 120–270 mT) in great contrast to the d-wave spectra (HcPC > 3 T) with the similar order of gap magnitude. We suppose that the s-wave pairing occurs near the Zn impurities.